THE BELANGAR TRADITION OF THE SASAK COMMUNITY: ARTICULATION OF RELIGIOUS VALUES AND SOCIAL SOLIDARITY - Fitria Sabila; Kamarudin Zaelani; Najamudin; Nazar Naamy (Tahiro : Journal of Peace and Religious Mederation, 2026)
The Belangar tradition is a cultural heritage practiced by the Sasak community in Lombok, reflecting a syncretism between Islamic values and local wisdom. This study aims to examine the role of Belangar in strengthening social solidarity and aligning religious values with local culture, employing the theory of religious-cultural syncretism and Durkheim's theory of collective ritual as the epistemological foundation for reading the relationship between ritual practice and social cohesion. Unlike previous studies on Belangar, which tend to be descriptive, this research offers novelty by exploring the internal tensions between Belangar practices and more puritanical religious views, as well as critically analyzing the adaptation of this tradition in the digital era. Utilizing a qualitative approach and case study methodology, data were collected through participatory observation, in-depth interviews, and documentary analysis. The findings indicate that Belangar serves not only as a religious ritual but also as a platform for enhancing social bonds within the community, involving various social strata, including the youth, who now leverage social media to promote this rich and meaningful tradition. The results depict the adaptation of the Belangar tradition in the face of modernization, where the use of digital technology helps maintain the relevance of local culture. This research underscores the importance of cultural education to ensure the continuity of local values in a modern context. As a symbol of unity and social concern, Belangar reflects the dynamics between culture and religion in the lives of the Sasak people.